Thermoelastic stability of closed cylindrical shell in supersonic gas flow. Issue 5 (September 2019) - Baghdasaryan, G.Y.; Mikilyan, M.A.; Vardanyan, I.A.; Marzocca, P.
Highlights: When the edges are free, a constant thermal field does not affect the value of flowing critical speed. Depending on the wave number, critical speed has a minimum point. Variability of temperature field has a significant effect on the value of the critical speed (it increases) and this effect increases with the increasing wave number. Critical speed as a function on wane number has a minimum point, which depends on variability of temperature field. Constant component of thermal field has a significant effect the stability of examined system. Positive temperatures narrow the area of stability and reduce the value of the critical speed. Moreover, there is a positive value of a constant temperature field above which the cylindrical shell becomes unstable. Negative constant temperature leads to the expansion of stability region and to an increase of the value of critical speed. Abstract: In this paper the problem of linear stability of a closed cylindrical shell under the action of both non-uniform temperature field and supersonic gas flow is considered. The stability conditions for the unperturbed state of the aerothermoelastic system are obtained. It is shown that, by the combined action of the temperature field and the ambient supersonic flow, the process of linear stability can be controlled and the temperature field affects significantly the critical flutter speed.